Evaluating wheat response to biostimulants: a 25-year review of field-based research (2000–2024) - Sellami, Mohamed Houssemeddine; Di Mola, Ida; Mori, Mauro (Frontiers in Sustainable Food Systems, 2025)
Wheat, a staple crop, faces numerous challenges due to climate change and the increasing demand for sustainable practices. Biostimulants, which enhance plant growth and resilience, have gained attention for their potential to improve wheat productivity in an environment-friendly manner. This study presents a comprehensive bibliometric analysis of field-based research on wheat's response to biostimulants under field conditions from 2000 to 2024. Analyzing 222 studies, the bibliometric analysis reveals a significant rise in research publications on biostimulants, with an annual growth rate of 15.6%. Asia leads with the largest share of publications (59.4%), followed by Europe (18.1%) and Africa (11.6%). North America, South America and Oceania have fewer contributions. Additionally, research institutions in Pakistan, India and Egypt rank as the most productive on this topic. Saudi Arabia stands out with the highest percentage of international collaboration, at 91.7% between countries and 100% among institutions. The findings reveal that biostimulants significantly improve wheat's ability to withstand abiotic stress, optimize nutrient uptake, and enhance overall plant health. Research is transitioning from traditional organic methods and microbial inoculants to advanced biostimulant formulations, improved nutrient management, and reduced environmental impact. However, gaps remain, particularly in understanding the combined effects of multiple biostimulants and their long-term impact on wheat and soil health. This synthesis of research trends lays the groundwork for advancing sustainable wheat production, supporting food security and agricultural resilience amidst environmental challenges.